(3cJGH GdgjFI GdSfjI aj GdgjFI GdSfjIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG eGde fcf fYde gPG cJGH ai Yde GdgjFI GbJHSJg ef GdBKGQ hJJHYJg ef GdCNHGQ eGhdG ai GdYQT hGdcQSi s
(3BNQgG (B:s
(3CNQL GdWHQGfi Yf eSde GdgLQfi bGd bdJ dYHO Gddg Hf YeQh Me Ndb bGd ef eGA hQjM hfhQ hXdeI aCJjJ GHf YHGS aSCdJg Yf Pdc abGd ajgG ceG bGd YHO Gddg Hf YeQh GfJgi hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2047s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs